2014
DOI: 10.1111/jhn.12220
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dropout in a group weight‐loss programme: a longitudinal investigation

Abstract: Weight-loss in the beginning of the programme is a crucial independent determinant of dropout in each week except the last one. This finding is important because it suggests a simple assessment for a major dropout risk factor in adult weight-loss intervention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
2
36
0
1
Order By: Relevance
“…Several researchers have previously demonstrated that initial weight loss is associated with study dropout in dietary based weight loss trials [9][10][11][12][13][14][15][16] , however this finding is not consistent and others have found no relationship 11,17,18 . This is the first study to quantify the amount of initial weight loss which predicts dropout and to investigate and quantify additional easily obtainable subject characteristics such as age which can be used to ensure adequate randomisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have previously demonstrated that initial weight loss is associated with study dropout in dietary based weight loss trials [9][10][11][12][13][14][15][16] , however this finding is not consistent and others have found no relationship 11,17,18 . This is the first study to quantify the amount of initial weight loss which predicts dropout and to investigate and quantify additional easily obtainable subject characteristics such as age which can be used to ensure adequate randomisation.…”
Section: Discussionmentioning
confidence: 99%
“…One month was the earliest time point at which weight was recorded in the weight loss trials studied here. Recent research has demonstrated that weight loss as early as one week 16 or BMI changes as early as two weeks may be predictive of dropout 10 and future research should investigate the role of weekly monitoring to quantify the risk of dropout.…”
Section: Discussionmentioning
confidence: 99%
“…33 One study also suggested that weight loss within the first two weeks of studies predicted retention. 19 While weight loss was a. Adjusted for body mass index, age, perceived stress score and partner enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%
“…11 Factors that have been identified as influencing retention in weightloss trials include age, sex, race, distance to intervention site, cognitive impairment, occupational status, education, socioeconomic status, smoking, physical activity level and depression. 9,[16][17][18][19] A review of 50 studies of AAs in clinical trials identified barriers to retention including lack of a study partner, lower educational level, and lack of compensation. 20 An earlier study conducted by our team found that a decentralized CBPR approach led to intervention…”
Section: Methodsmentioning
confidence: 99%
“…Individuals are more likely to drop out of trials if they are not meeting weight loss goals (Yackobovitch-Gavan et al, 2015). Two important determinants of weight loss via eHealth interventions include frequency of logins and including interactive intervention components (Gold et al, 2007).…”
Section: Strengths and Challenges Of Ehealth Weight Management Studiesmentioning
confidence: 99%